Lesbian texts and contexts: Radical revisions - Jay, Karla; Glasgow, Joanne (Feminist crosscurrents, 1990)
Lesbian writers include some of the most innovative and adventurous writers of this century, but only recently have they been given their due attention in terms of critical study. This book is the first anthology to discuss the subject of lesbianism as it relates to the critical interaction among readers, writers, and literary critics. It explores lesbian texts in terms of identification, meaning, and interpretation, and examines the complex entanglements of identity, voice, intersubjectivity, textualities, and sexualities.
Keywords: amériques; anthologie; approches et analyses; arts; discipline; lesbianisme; littérature; outils; ouvrages de références; personnes lesbiennes; régions géographiques; états-unis; études littéraires

Dykewords: An anthology of lesbian writings - Lesbian Writing and Publishing Collective. (Women's Press, 1990)
An entertaining and refreshing anthology that includes writing about the vibration of lesbian love, cultural identity, sexual fantasy, overcoming alcohol abuse, a teenage coming out, lesbian history, imaginative lesbian antics for lesbian survival and much, much more
Keywords: anthologie; approches et analyses; corps; histoire et politique; identités LGBTQIA2+; littérature; outils; ouvrages de références; personnes lesbiennes; poésie; racisme; ressource en ligne; roman; santé; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques